Translational regulation by ribosomal protein S8 in Escherichia coli: structural homology between rRNA binding site and feedback target on mRNA. - Olins, P O (1981)
It has been previously shown that ribosomal protein synthesis in Escherichia coli is regulated at the level of translation by certain key ribosomal proteins. In the spc operon, S8 regulates the expression of L5 and some of the subsequent genes, while the first two genes (L14 and L24) are regulated independently. We therefore determined the DNA sequence at the junction of the L24 and L5 genes, which corresponds to the putative feedback target for S8. We show that there is a striking homology between the structure of the mRNA for this region and the known binding site for S8 on 16S rRNA. These results support the theory that the regulation of ribosomal protein synthesis is based on competition between rRNA and mRNA for regulatory ribosomal proteins.